Research on University-Enterprise Cooperation Model in Higher Vocational Education for Private Enterprises to Go Global - Liu, Wen (Journal of Research in Vocational Education, 2025)
At present, as China's reform and opening-up deepen and the global market becomes increasingly open, private enterprises have gradually emerged as the main force in China's international economic exchanges and cooperation. Many outstanding private enterprises actively respond to the national call and actively seek development in overseas markets. Nevertheless, in the process of internationalization, talents have become one of the crucial guarantees and core competitiveness for private enterprises to successfully go abroad. For vocational colleges, their training objectives are precisely defined, oriented towards serving industrial development and social demands, and cultivating talents with an international vision and high-level vocational skills, which has become a key link in promoting the ‘going-out’ strategy of private enterprises. Hence, it is particularly urgent and significant to establish a talent training system in the vocational education domain that can effectively support private enterprises to go global. This paper will conduct in-depth exploration and analysis of the current talent status of private enterprises' overseas expansion, and in response to the current difficulties and problems, construct and propose the university-enterprise cooperation model of One Core, Double Approach, and Three Integration, thereby empowering private enterprises as an important force for overseas development and enhancing the quality and capability of talents for private enterprises to go global.